2017
DOI: 10.1007/s10067-017-3725-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective analysis of disease-modifying anti-rheumatic drugs in rheumatoid arthritis

Abstract: The main objective of the study was to perform the pharmacoeconomic analysis of synthetic disease-modifying anti-rheumatic drugs in rheumatoid arthritis patients. A prospective, observational study was conducted in 98 rheumatoid arthritis (RA) patients meeting 2010 Rheumatoid Arthritis Classification Criteria. Treatment-naive RA patients were initiated on synthetic disease-modifying anti-rheumatic drugs (DMARD/s) and followed up for 3 months. Average cost-effectiveness analysis was done by taking Health Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The relationship between the high costs of pharmacological treatment of RA patients and the lack of persistence or adherence throughout follow-up demonstrates the difficulties that health systems have in covering this pathology, especially in developing countries, which have limited resources and which need to select cost-effective therapies based on their own analysis that guarantee access and coverage that are also safe and improve the quality of life of those who require them [38,39]. Undoubtedly, the problems of lack of persistence in the use of antirheumatic drugs deserve special attention, which leads to the need to search for strategies that identify the causes and improve adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the high costs of pharmacological treatment of RA patients and the lack of persistence or adherence throughout follow-up demonstrates the difficulties that health systems have in covering this pathology, especially in developing countries, which have limited resources and which need to select cost-effective therapies based on their own analysis that guarantee access and coverage that are also safe and improve the quality of life of those who require them [38,39]. Undoubtedly, the problems of lack of persistence in the use of antirheumatic drugs deserve special attention, which leads to the need to search for strategies that identify the causes and improve adherence to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies conducted in different settings have reported similar female predominance in their study varying between 76.7% and 87%. [ 4 5 6 7 8 ] The reasons for this feminine predominance in auto-immune diseases are not clear, though genetic (X-linked) factors and hormonal relation have been attributed. [ 9 10 ] In the present study, the median age was 48 years which was comparable to other studies which showed that the peak prevalence of RA was in fifth decade.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 10 ] In the present study, the median age was 48 years which was comparable to other studies which showed that the peak prevalence of RA was in fifth decade. [ 4 6 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations